Pengaruh Penambahan Kombinasi Kadar Cairan Anti Rayap Dan Aspal Terhadap Kinerja Perkerasan Daur Ulang AC-WC - Suilman, M. Jejen; Malik, Alfian; Alwinda, Yosi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Recycling techniques for pavement construction are reuse of existing pavement construction materials, which are reprocessed either with or without adding new materials. Old road Pavement is usually called Reclaimed Asphalt Pavement (RAP). AC-WC (Asphalt Concrete - Wearing Course) is a layer of pavement that is directly contacted to vehicle tires. The purpose of this study was to determine the effect of adding anti termite and asphalt penetration 60/70 towards Marshall characteristics on concrete asphalt mixture (AC-WC). In this study, the termite and asphalt penetration 60/70 were added as fluxing material from RAP material. The bitumen content obtained from the RAP material used is 6%. The anti-termite and asphalt penetration levels of 60/70 used in this study were 0.5%, 1%, 1.5% and 2% for mixed weight. The specifications used in this study were following General Spesification of Bina Marga 2010 (3rd Revision) using the Marshall method. From the results of testing the Marshall characteristics it can be concluded that the VMA and VFA values increase along with the addition of added material levels, while the VIM value and stability decrease with the addition of added material levels and for irregular flow and MQ values. The results of the VIM, VMA, VFA, stability and MQ values meet the spesification, while the value of flow is vice versa. Optimum Additives Content (KBTO) cannot be found because the flow value does not meet the specification. Keywords: Termite, Aslphalt, AC-WC, General Spesification of Bina Marga 2010 the 3rd Revision